Assessment of management effectiveness at Belum Rainforest Resort (BRR), Malaysia; with special focus on process - Hassan, Mohamad Ghozali; Abdullah, Shahmir Sivaraj; Abdullah, Rohani (2013)
Presently, most of the countries in the world are concerned about environmental degradation.One of the avenues to protect the environment is the active promotion of ecotourism which shows a growing niche market within the big travel industries and possesses the potential of being an important sustainable developmental tool.Of all the acitivities conducted by the management of ecotourism, process of development and management are found lacking, and this has a great impact on the intention of creating and developing ecotourism in a country.The absence of proper process of management in ecotourism calls for the implementation process in ecotourism which is crucial in developing ecotourism, particularly in Belum Rainforest Resort in Malaysia.Moreover,the research made use of qualitative research approach involving the use of secondary data that relate to the process of assessing management effectively.The result showed that process determines whether or not the best systems and processes for management are in use.Consequently,well-planned protected areas need sound management processes if they are to be effective.